2011
DOI: 10.1007/s00226-011-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Liriodenine from Michelia formosana heartwood against wood-rotting fungi

Abstract: Wood-rotting fungi lead to great economic losses of lignocellulosic materials. The influence of extractives on the decay resistance of Michelia formosana wood and the antifungal activities of heartwood extract and its constituent against wood-rotting fungi were evaluated. Results revealed that extractives had a strong influence on the decay resistance of M. formosana heartwood. The unextracted heartwood block was resistant to fungi, while the extracted heartwood block was not. Antifungal activities of ethanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Glaucine 68 isolated from the aerial component of Glaucium oxylobum showed moderate skin anti-fungal activities against Microsporum canis, Microsporum gypseum, and Trichophyton mentagrophytes [93]. Antifungal activities of the non-Annona isolated alkaloids were evaluated against non-pathogenic fungi including liriodenine 11 from the wood of Michelia formosa which indicated a low activity against several wood decaying fungi both white and brown rot-fungi, Lenzites betulina, Trametes versicolor, Laetiporus sulphureus, Gloeophyllum trabeum, and Fomitopsis pinicola [94]. Similar alkaloids were also previously evaluated against pathogenic bacteria, including liriodenine from the roots of Zanthoxylum nitidum which showed a good antimicrobial activity against MRSA with MIC value of 93.8 µg/mL [95].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Glaucine 68 isolated from the aerial component of Glaucium oxylobum showed moderate skin anti-fungal activities against Microsporum canis, Microsporum gypseum, and Trichophyton mentagrophytes [93]. Antifungal activities of the non-Annona isolated alkaloids were evaluated against non-pathogenic fungi including liriodenine 11 from the wood of Michelia formosa which indicated a low activity against several wood decaying fungi both white and brown rot-fungi, Lenzites betulina, Trametes versicolor, Laetiporus sulphureus, Gloeophyllum trabeum, and Fomitopsis pinicola [94]. Similar alkaloids were also previously evaluated against pathogenic bacteria, including liriodenine from the roots of Zanthoxylum nitidum which showed a good antimicrobial activity against MRSA with MIC value of 93.8 µg/mL [95].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Moreover, some highly reactive wood compounds (known as extractives) are released primarily during wood degradation processes. Some studies have reported the toxicity and antifungal activity of these molecules (4)(5)(6)(7). This suggests that during wood degradation, fungal cells are under oxidative stress.…”
mentioning
confidence: 99%
“…formosana is an evergreen tree mainly distributed in Taiwan, Japan, and Ryukyu Islands [1]. In the previous literature, its heartwood exhibited high resistance against rots due to the presence of liriodenine [6]. The chemical investigations of leaves [5,7], barks [8], root barks [2], root wood [4], heartwood [9,10], stems [11], and pericarps [12] have been reported, but the anti-inflammatory and cytotoxic properties of constituents from heartwood are not known.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the extract of Michelia champaca leaves has also exhibited an anti-inflammatory activity in pro-inflammatory conditions [ 3 ]. Moreover, the aporphine alkaloid and sesquiterpene lactone constituents of this genus have caused a great interest due to their diverse structures and significant biological activities [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%